Action of the chymosin enzyme in milk: proposing a simple and low-cost experiment for the teaching of Biochemistry in the Biology discipline (Research, Society and Development, 2022)
Biochemistry is a fascinating area of Biology, and it is concerned with studying the interactions of organic and inorganic molecules in the biological systems of living beings. However, it is a complex area endowed with many terms and processes, often abstract, which can be an obstacle to the context of students. In this sense, in order to overcome such obstacles, this work has as main objective to facilitate and instigate the learning of students in the discipline of Biology in high school in the proposal of an experimental activity of the enzymatic action of chymosin in milk, using simple and low-cost materials. Students will be invited to experience, discuss and discuss with the teacher, a series of experiments, allowing to contextualize and apply what was learned in theoretical classes of Biology, regarding Biochemistry, especially in matters related to proteins, enzymes, denaturation and factors that affect its catalytic efficiency. In addition to these topics, it will be possible to discuss with students the mechanism of cheese making. We believe that the practice of this experimental activity can demystify that Biochemistry is a complex area, allowing to motivate and facilitate student learning in the proposed theme, in addition to promoting the perspective of scientific experimentation.